2014
DOI: 10.1021/ol5030019
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic [2 + 2 + 2] Cycloaddition of Benzothiophene Dioxides with α,ω-Diynes for the Synthesis of Condensed Polycyclic Compounds

Abstract: A Rh-catalyzed intermolecular [2 + 2 + 2] cycloaddition of the 2,3-double bond of benzothiophene dioxides with α,ω-diynes gave sulfone-containing cycloadducts in high yields. This is the first example of a catalytic [2 + 2 + 2] cycloaddition that uses the 2,3-double bond of a heterole as an ene moiety. The consecutive reaction of benzodithiophene tetraoxide with 2,3-naphthylene-tethered 1,7-diyne gave an 11-ring condensed polycyclic compound in one pot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Eur.J.2016, 22,6720 -6739 www.chemeurj.org yields. [30] Secondly, an enantioselective reactionu sing 1,1-disubstituted alkenes as an ew strategy for the construction of quaternary carbon stereocenters is shown. With exo-methylene cyclic compounds as substrates, chiral spirocyclic structures were synthesized.…”
Section: Scheme14 Asymmetric Cycloaddition Of Diynes With Norbornenementioning
confidence: 99%
See 1 more Smart Citation
“…Eur.J.2016, 22,6720 -6739 www.chemeurj.org yields. [30] Secondly, an enantioselective reactionu sing 1,1-disubstituted alkenes as an ew strategy for the construction of quaternary carbon stereocenters is shown. With exo-methylene cyclic compounds as substrates, chiral spirocyclic structures were synthesized.…”
Section: Scheme14 Asymmetric Cycloaddition Of Diynes With Norbornenementioning
confidence: 99%
“…Two recent examples are depicted in Scheme . Firstly, the 2,3‐double bond of benzothiophene dioxides was used as the olefinic partner in the reaction with with α,ω‐diynes to give sulfone‐containing cycloadducts in high yields . Secondly, an enantioselective reaction using 1,1‐disubstituted alkenes as a new strategy for the construction of quaternary carbon stereocenters is shown.…”
Section: Rhodium and Iridium Catalysismentioning
confidence: 99%
“…On the other hand, cationic rhodium(I)/biaryl bis‐phosphine complexes are highly active and selective catalysts for the [2+2+2] cycloaddition of α,ω‐diynes with cyclic alkenes, such as norbornene, benzothiophene dioxides, 2,3‐dihydrofuran, cyclopentene, indene, and acenaphthylene . Herein, we found that a cationic rhodium(I)/SEGPHOS complex was able to catalyze the [2+2+2] cycloaddition of biphenyl‐linked diynes with 2 a and 2 b (Scheme , bottom) .…”
Section: Introductionmentioning
confidence: 99%
“…4 Consequently, much effort has been made in developing general methods for the construction of benzothiophene dioxide frameworks. Most of the synthetic endeavors to assemble these compounds involve Rh-catalyzed [2 + 2 + 2] cycloadditions of alkynes, 5 photochemical cyclization of o -tolualdehydes, 6 catalytic Garratt–Braverman cyclization of dipropargyl sulfones, 7 Rh-catalyzed C–H insertion of α-diazo-β-arylmethanesulfonyl esters, 8 and Pd-catalyzed intramolecular arylations of enolates. 9 Recently, Wu et al.…”
Section: Introductionmentioning
confidence: 99%